PENERAPAN GAME BASED LEARNING MENGGUNAKAN ZEP DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS XI PADA MATERI JARINGAN KOMPUTER DAN INTERNET DI MAN 2 SAMARINDA - Rafli Risyaputra, Muhammad; Aloyshima Haris, Celine (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background to this research is based on the low student learning outcomes in Informatics and the predominant use of lecture methods, which lack active student participation in the learning process. Furthermore, the lack of use of technology-based learning media makes it difficult for students to understand the material, particularly on computer networks. This study aims to determine the application of the Game-Based Learning model using the ZEP Quiz media on student learning outcomes in Informatics for 11th graders at MAN 2 Samarinda. This research is an experimental study with a pre-experimental design using a one-group pretest-posttest design. The study involved 11th grade students as subjects. The instruments used included a pretest and posttest to measure student learning outcomes, as well as a student response questionnaire to assess responses to the learning process. The results showed an increase in student learning outcomes after the implementation of the Game-Based Learning model using the ZEP Quiz media. This was demonstrated by an average pretest score of 69.29 and an average posttest score of 89.57. The N-Gain analysis showed an average value of 66.77%, which is in the moderate category, indicating a fairly effective increase in learning outcomes. Furthermore, student responses to the learning process were positive, indicating that the use of the ZEP Quiz media was able to increase student interest and engagement in the learning process.